How benefits management helps balanced scorecard to deal with business dynamic environments - Jorge Gomes; Mário Romão (Tourism & Management Studies, 2013)
In the rapidly-changing environments characterizing most industries today, organizations face intense competitive pressure to do things better, faster and cheaper. The business environment of the 1990s has been subjected to rapid and accelerated change that creates more and more uncertainty and complexity. Most markets are becoming increasingly dynamic. Organizations can no longer rely on a traditional analytical approach to understand their industry or market, since that market is changing in rapid and unexpected ways. In spite of its worldwide dissemination, Balanced Scorecard (BSC) has demonstrated inadequacy in certain circumstances. Some of the original advantages of the BSC can nowadays be interpreted as weaknesses. We suggest that in business dynamic environments the benefits management approach, by using the benefits dependency network can help BSCs to guide and support the benefits achievement related with investments, in a complementary way. By using a case study we try to show how a BSC exhibits limitations to deal with business disruptive environments and how a benefits management approach brings a strengthened business implementation vision, from strategy down to operations.